The Use of the Alef Education Platform as an Interactive Media in Arabic Language for Science and Technology Materials: Penggunaan Platform Alef Education Sebagai Media Interaktif Bahasa Arab Terhadap Materi Ilmu Pengetahuan dan Teknologi - Yuyun Rohmatul Uyuni; Nuroh Nuroh; Siti Shalihah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
Alef Education is an interactive digital platform that offers various innovative learning tools and resources. Arabic language learning using the Alef platform is shown as technology-based learning to meet the needs of the learning system in madrasas. The technology used by students is mobile phones, computers, and laptops by having a good quota and network, students can bring one of these technologies to the madrasah for learning. The platform creates a personalized learning experience for students to play an important role as well as help students achieve better learning outcomes. The platform supports teachers by providing engaging content and games that are appropriate to the curriculum, aiding in student assessment and management. This study aims to find out how to use the Alef Education platform as an interactive media in Arabic, especially for Science and Technology (IPTEK) materials. The research method used is a literature review approach with a descriptive qualitative method. This research data was collected using the library research technique, which is a literature study by reading books, articles, and other data sources in the library. Also, in the form of documentation of the features of the Alef Education platform and various development tutorials on the use of Alef Education learning media available on the Website. The data analysis technique used in this study is content analysis, which is research that is an in-depth discussion of the content of written or printed information and then concludes based on the data that has been collected and analyzed. The results of this study show that Alef Education can be used as a medium and tool for learning Arabic for "Science and Technology" material, of course, it can be used by teachers and students with various features that the Alef Education platform can increase interactive learning skills and students' interest in learning Arabic. Keywords: Alef Education, Arabic, Media, Technology